Annual Bluegrass (Poa annua) Control in Glyphosate-Resistant Perennial Ryegrass Overseeding. (March 2014) - Flessner, Michael L.; McElroy, J. Scott; Wehtje, Glenn R.
Abstract : 'Replay' and 'JS501' perennial ryegrass cultivars have been conventionally bred for reduced sensitivity to glyphosate, potentially allowing the herbicide to be used for selective weed control in overseeded bermudagrass. Field experiments were conducted to evaluate optimal glyphosate application rate, regime (single and sequential applications), and timing for annual bluegrass control in bermudagrass overseeded with these cultivars. Additionally, greenhouse experiments were conducted to compare the sensitivity to glyphosate of Replay and JS501 to susceptible cultivars 'Caddy Shack' and 'Top Gun II' through log-logistic rate-response analysis. In field experiments, only two treatments resulted in > 90% annual bluegrass control and < 25% perennial ryegrass injury. These two treatments were a single application of 280 g ae ha −1 glyphosate in January and 140 g ha −1 followed by an additional 140 g ha −1 applied in January. Perennial ryegrass cultivars were compared using 50% inhibition ( I 50 ) values, i.e. 50% visible estimates of injury or 50% reduction in clipping weight. I 50 values obtained 6 wk after treatment from injury data were 2.56, 2.64, 0.81, and 0.84 g ha −1 glyphosate for Replay, JS501, Caddy Shack, and Top Gun II, respectively. Replay and JS501 were similar in sensitivity to glyphosate and were up to four times more tolerant than Caddy Shack and Top Gun II across rating dates and data types.